Irregular Shaped, Assumably Semi‐Crystalline Calciumphosphate Platelet Deposition at the Mineralization Front of Rabbit Femur Osteotomy: A HR‐TEM Study. Issue 3 (16th August 2012) - Grüner, Daniel; Lips, Katrin S.; Heiss, Christian; Schnettler, Reinhard; Kollmann, Theresa; Simon, Paul; Kniep, Rüdiger
Summary Although bone minerals have been widely studied by various techniques in previous studies, crystal structures, morphology of bone minerals and its building pathway remained still controversy. In this work, the ultrastructure of the mineralization front of rabbit femur has been studied by conventional and high‐resolution (HR) transmission electron microscopy (TEM). In order to induce a healing and demineralization process the animals were subjected to a standardized osteotomy stabilized with titan screws and sonic pins. After 84 days follow‐up time the newly build bone was investigated. The mineralization front of rabbit femur osteotomy contains partly mineralized collagen fibrils with a pronounced striped pattern together with a large number of agglomerated apatite platelets. The striation is caused by mineralization in the hole zones of the collagen fibrils, corresponding to the early stage of mineralization. In the TEM micrographs, the mineralization zone appears denser and compact when compared with fully mineralized bone, although most of the collagen fibrils are completely mineralized in the latter (higher concentration of interfibrillar apatite platelets within the mineralization zone). In bone some partly mineralized collagen fibrils are also observed, revealing the same arrangement, regular shape, and size of apatite platelets as collagen fibrils in the mineralization zone. Apatite platelets with irregular shapes are observed at the vortex‐shaped outer boundary of the mineralization zone, i.e. at the interfaces with nonmineralized collagen or osteoblasts. HR TEM micrographs reveal that the platelets are assumably semicrystalline and that within the platelet nanocrystalline domains of apatite are embedded in an amorphous calciumphosphate matrix. SCANNING 35: 169‐182, 2013. © 2012 Wiley Periodicals, Inc.